Peningkatan Produktifitas Usaha Keripik Singkong Melalui Pendampingan Teknologi di Desa Geneng Kabupaten Jepara - Muhammad Abid Birrul Jabbar Shobir; Decky Rochmanto; Ahmad Ainur Rifqi; Dawam Khusnu Chuluq; Fery Irawan; Linda Yuliana; Melina Indah Susanti Azzahro; Muhammad Andriyan Saputra; Muthmainatus Tsaniah; Nita Lutfiana; Siti Yulia Zusnita (Universitas Islam Nahdlatul Ulama Jepara, 2022)
Cassava chips are one of the snacks favored by residents because of their crunchy texture and can be enjoyed in any circumstances while relaxing. However, most cassava chips entrepreneurs still use packaging that is fairly monotonous and old-fashioned so that cassava chips are mostly only enjoyed by the elderly. This was also experienced by the partners chosen by the Geneng Village Community Service Team. The packaging used by partners is still in the form of clear plastic with a piece of paper inside that says